A quaternion-based augmenting method dedicated to biometric gait systems - Sawicki, Aleksander; Saeed, Khalid (Zielona Góra: Uniwersytet Zielonogórski)
Collecting large amounts of real-world data can be expensive, time-consuming, or even impossible in some cases. This situation can be particularly acute for IMU-based gait-analysis data due to participant fatigue, changing walking surfaces, and instrumentation positioning. These factors can provoke changes in the characteristics (drift or distribution shift) of data collected over long durations or on different days, making analysis difficult. Ideally, one would prefer a larger data set whose distributional characteristics do not change.
Keywords: biometrics; MEMS; CNN; augmentation